(untitled) (Challenges of the Future, 2025)
Research Questions (RQ): What factors do men and women think influence the quality of their reproductive health? What differences exist between men and women in their perception of their own reproductive health? How do stigmas and taboos affect reproductive health? Purpose: The purpose of this research was to examine the perspectives of men and women in the process of reproductive health care. Method: Qualitative method was used. Data was collected from a purposive sample through semi-structured interviews conducted in four focus groups. The data was analyzed using content analysis. Results: Results: three themes were identified through the qualitative analysis method: (1) reproductive health of men and women, (2) socio-cultural aspects of reproductive health, and (3) challenges of reproductive health. At the same time, 13 sub-themes were identified. The study showed that primary socialization has a significant impact on an individual’s attitudes towards reproductive health in adulthood. It was found that women are more concerned about reproductive health than men. It was also found that stigmas and taboos, which prevent open discussion about reproductive health, have a major impact on the quality of reproductive health. This leads to lack of information, fear, discrimination and inequalities in access to health services. Organization: The research highlights the need for more education and emphasis on preventive care and reducing social exclusion and stigma related to reproductive health. Society: The results of the research contribute to a better understanding of men’s and women’s perceptions of reproductive health and how they think it is influenced by society. In this context, it also provides a better understanding of how stigmas and taboos affect reproductive health and how to seek help when reproductive health problems arise. Originality: The research provides insights into the specific nature of men’s and women’s reproductive health and how society views it. The originality of the research is that it offers a broad insight into how men and women understand reproductive health. It also provides an outline of the current state of reproductive health in society. Limitations/Future Research: The answers obtained from the interviewees are subjective in nature and are subject to interpretation by the researchers. It would be useful to conduct quantitative type of studies in the future. Also, one of the limitations is related to the research sample, which includes a set of interviewees from two Slovenian regions. In the future, it would be necessary to include interviewees from the whole of Slovenia so that the results can be generalized to the whole population.